MDM2 expression in the progression of Barrett’s oesophagus - Robinson, Leora; Ilyas, Mohammad; Ragunath, Krish; Card, Timothy R.; Abradu-Berchie, Berice; Kaye, Philip (Wiley, 2018)
Barrett's oesophagus (BO) is the main precursor for oesophageal adenocarcinoma (OAC), and dysplasia arising within it is the standard marker used to predict risk of malignant progression. However, dysplasia diagnosis is subject to a significant amount of interobserver variation. Biomarkers may aid the diagnosis of dysplasia and may help predict the risk of progression to OAC. Abnormal expression of p53 can be reproducibly detected by immunohistochemistry (IHC) and it is an effective marker of risk of OAC1. There is however still a need for additional early stage markers.